Strategy For Developing The Onion (Allium Fistulosum) Farming Business In California Agrotourism In Cialam Jaya Village, Konda District, South Konawe Regency - Cecep Julian Dwi Akbar Jaimal; Samsul Alam Fyka; Hadi Sudarmo (International journal of technology and education research, 2026)
The development of a spring onion (Allium fistulosum) farming business at the California Agrotourism site in Cialam Jaya Village, Konda District, South Konawe Regency, is a strategic effort to increase agricultural productivity and diversify the agrotourism-based economy. This study aims to formulate a sustainable spring onion farming business development strategy by considering internal strengths and weaknesses, as well as external opportunities and threats faced by farmers in the study area. The methods used in this study include primary and secondary data collection, as well as a SWOT analysis to evaluate the current state of spring onion farming and formulate optimal development strategy alternatives. The analysis indicates that effective development strategies include increasing farmer capacity through training and technical guidance on spring onion cultivation, improving market access through partnerships and digital marketing, diversifying derivative products to expand added value, and strengthening the agrotourism function as an educational and recreational platform. Implementation of this strategy is expected to increase farmer income, strengthen farming business resilience, and enhance the attractiveness of California Agrotourism as an educational tourism destination in South Konawe.